2009
DOI: 10.3354/meps08247
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of molluscan assemblages in mangroves by the fucalean alga Hormosira banksii

Abstract: The fucalean macroalga Hormosira banksii facilitates diverse rocky intertidal communities. Along the east coast of Australia, the alga can also persist in mangroves as a free-living form trapped amongst pneumatophores. We investigated (1) whether the alga has an effect on molluscan species richness and abundance in mangroves similar to that on rocky shores, and (2) whether, in mangroves, the source (phenotypically distinct estuarine or rocky shore populations) of H. banksii influences the outcome of its inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…The H. banksii used for experimental manipulations was from the surrounding mangrove forest and was defaunated by hand prior to reintroduction to plots at appropriate experimental biomasses. To ensure that H. banksii was retained at the experimental density, but that epifauna could still colonize, we erected a galvanized mesh fence around each plot with a 50-mm gap at the base (see Bishop et al 2009). The fences were 200 mm high and were constructed of 5-mm galvanized mesh held in place by three plastic stakes 450 mm long.…”
Section: Direct Effects Of Pneumatophore Density and Hormosira Banksimentioning
confidence: 99%
See 1 more Smart Citation
“…The H. banksii used for experimental manipulations was from the surrounding mangrove forest and was defaunated by hand prior to reintroduction to plots at appropriate experimental biomasses. To ensure that H. banksii was retained at the experimental density, but that epifauna could still colonize, we erected a galvanized mesh fence around each plot with a 50-mm gap at the base (see Bishop et al 2009). The fences were 200 mm high and were constructed of 5-mm galvanized mesh held in place by three plastic stakes 450 mm long.…”
Section: Direct Effects Of Pneumatophore Density and Hormosira Banksimentioning
confidence: 99%
“…In southeastern Australia, the dominant species of mangrove, Avicennia marina, produces pneumatophores (aerial roots) that facilitate many species of mollusks and crustaceans by providing structure, shelter, trapping detrital material, and supporting growth of epiphytic algae (Beck 1998, Skilleter and Warren 2000, Ross 2006). Among the species facilitated by A. marina is the fucalean macroalga, Hormosira banksii (King 1981, King andWheeler 1985), which is itself an important foundation species (e.g., Bishop et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The relative contribution of foundation species to ecosystem function may stem from their morphological structure which has been measured using a composite of species鈥恠pecific trait鈥恇ased metrics such as size, number of branches or size of air bladders (Bishop et al . ; Bishop, Fraser & Gribben ; Wright et al . ) and mathematical relationships of species complexity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The structure provided the pneumatophores traps free-living and reproductively capable H. banksii that washes into the mangrove forest following detachment from rocky shores (Plate 1, Appendix A; McKenzie and Bellgrove 2008). The alga, which is characterized by a distinctive thallus of branched chains of vesicles, in turn, supports dense and diverse communities of epifaunal mollusks (Plate 1, Appendix A; Bishop et al 2009Bishop et al , 2012. Experiments independently manipulating the density of pneumatophores and the biomass of algae in a crossed design have shown that this indirect effect of pneumatophores on epifauna, arising via the cascade, overwhelms their direct effects (Bishop et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…H. banksii vesicle diameter and length vary by as much as 20 mm, and thallus length by tens of centimeters (Womersley 1987, Ralph et al 1998, Macinnis-Ng et al 2005. The morphology of the alga directly influences epifaunal colonization (Bishop et al 2009), but it is unclear whether it also influences algal retention by pneumatophores.…”
Section: Introductionmentioning
confidence: 99%